The Qur’an and Digital Da’wah : A Thematic Study on Religious Communication Strategies in the Age of Technological Disruption (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
The rapid advancement of technology in the age of disruption has significantly transformed patterns of religious communication, particularly in the context of Islamic da’wah. This study adopts a thematic approach to explore Qur’anic-based strategies that are adaptable to digital platforms. It integrates the Islamic epistemological frameworks of bayani (textual reasoning), burhani (rational reasoning), and irfani (intuitive-spiritual reasoning) to identify core da’wah principles: wisdom (hikmah), sincere exhortation (maw‘idzah), and respectful dialogue (mujādalah). These principles are analyzed in relation to their practical application through various forms of digital media, including social networking platforms, podcasts, and interactive video content. Relevant Qur’anic verses are examined to highlight values such as communicative ethics, emotional intelligence, and contextual sensitivity, which serve as guidelines for formulating adaptive da’wah strategies in the digital sphere. The findings suggest that effective digital da’wah requires not only technical fluency and mastery of communication tools, but also spiritual authenticity and epistemological depth. Balancing the timeless revelatory essence of the Qur’an with the adaptability required by modern media can foster communication that is inclusive, contextually relevant, and transformative. Furthermore, the research emphasizes that contemporary da’wah should avoid superficial engagement by grounding messages in a holistic understanding of Qur’anic guidance while utilizing creative and interactive formats. This synthesis of tradition and innovation ensures that the delivery of Islamic messages remains impactful, ethically grounded, and responsive to the needs of diverse audiences. In conclusion, digital da’wah is most effective when it harmonizes the enduring wisdom of revelation with the dynamic opportunities of technological communication, thus enabling a message that resonates across both spiritual and digital landscapes.